Injection of gel systems for CO2 leakage remediation in a fractured reservoir. (11th November 2021) - Zhu, Peixi; Tavassoli, Shayan; Ryu, Jenny; Pyrcz, Michael; Balhoff, Matthew T.
We perform a reservoir simulation study to investigate injection of gel systems, including cross-linked polymer gels and silica gels, as a treatment method for fracture sealing and leakage remediation in CO2 storage reservoirs. An adsorption and permeability reduction approach was adopted to model the fracture sealing by the gel. The results show that for both gel systems a successful treatment can reduce CO2 leakage by 10 3 times over 25 years of post-treatment CO2 injection. The effects of operating conditions, reservoir heterogeneity, and associated uncertainty on the treatment results were investigated by changing the injection time, injection rate, cross-linked polymer or silica concentration, reaction frequency factor, average reservoir permeability, and spatial correlation length. The simulation results show that selecting the appropriate operating conditions for specific reservoir properties are important to the success of CO2 leakage remediation. [Received: March 23, 2020; Accepted: November 15, 2020]